Government Policy to Accelerating Legal Certainty of Land Through Complete Systematic Land Registration (PTSL) (Studies in Kendal District Land Office) - Siti Sulistiyah; Umar Ma’ruf (Jurnal Daulat Hukum, 2019)
Problems in this study: (1) How is the implementation of activities in the District Land Office PTSL Kendal? (2) How the Government's policy to accelerate the legal certainty Landrights through PTSL ?. The method used in this research is the method of approach to socio-legal research, consisting of socio research and legal research. The results of this study are: (1) Implementation PTSL in Kendal District Land Office begins by planning activities PTSL by the Head of the Kendal District Land Office with pre inventory candidate and potential participants. (2) Government policy in speeding up the legal certainty of land rights through PTSL is based in Kendal land that already has a certificate covering an area of 13834.46 hectares.Suggestions in this study is consistent with the objectives of land registration is to provide certainty and legal protection to the rights holder, to reduce the escalation of disputes continues to grow, it is time for a land registration system through PTSL changed to positive land registration system.Keywords : Government Policy; Legal Certainty of Land Rights; PTSL.